High-Risk Families and Early Detection: Screening Awareness and Compliance in First-Degree Relatives of Oral Squamous Cell Carcinoma - Ali, Iqra; Sherjan, Hameeda; Zahid, Sumayya; Jawed, Wajida; Fatima, Tehreem; Faraz, Syed Abul; Khero, Rabail (Journal of Neonatal Surgery, 2025)
Background: Oral squamous cell carcinoma (OSCC) is a leading malignancy worldwide, strongly linked to tobacco, betel quid, and alcohol consumption. First-degree relatives (FDRs) of OSCC patients are considered a high-risk group due to shared genetic susceptibility and environmental exposures. Objectives: The objectives of this study were to assess awareness of OSCC and its risk factors among first-degree relatives of OSCC patients, to evaluate compliance with recommended oral cancer screening practices, and to identify barriers and facilitators influencing participation in screening programs. Methods: This cross-sectional descriptive study included 110 first-degree relatives (parents, siblings, and children) of histopathologically confirmed OSCC patients. Data were collected using a structured questionnaire assessing awareness, screening compliance, and perceived barriers and facilitators. Results: The mean age of participants was 39.8 ± 12.5 years; males comprised 56.4%. Children formed the largest group of relatives (40%). Overall, 60.9% had heard of oral cancer, while 47.3% recognized tobacco, 34.5% betel quid/areca nut, and 28.2% alcohol as risk factors. Awareness of early warning signs was reported by 34.5%. Only 21.8% had ever undergone screening and 10.9% received periodic check-ups, though 67.3% expressed willingness for future screening. Education level was significantly associated with both awareness (p = 0.01) and compliance (p = 0.03). Major barriers included lack of awareness (38.2%), financial constraints (25.5%), and fear of diagnosis (18.2%), while family history (40.0%) and physician recommendation (34.5%) were key facilitators. Awareness was strongly associated with willingness for screening (80.6% vs. 46.5%, p = 0.002). Conclusion: It is concluded that first-degree relatives of OSCC patients have limited awareness and poor compliance with screening, despite high willingness for future participation. Education is the strongest determinant of preventive behavior, while barriers are primarily informational and financial